CONSTRUCTING THE DIGITAL SKILLS CRISIS: A CRITICAL CONCEPTUAL HISTORY OF “SKILL” - Cooper, Zane; Bridges, Lauren E.; Ticona, Julia (AoIR Selected Papers of Internet Research, 2021)
There is a digital skills crisis: the digital skills crisis does not exist. Through a conceptual history of skill––a word, concept, and action––this paper analyzes the historical, cultural, and material constructions of skill and how it has come to influence current discourse around the alleged “digital skills crisis”. Rather than an intrinsic quality to be acquired, we show how skill has been deployed as a political concept to order bodies and processes according to the interests of power and capital. Pushing back against skilled/unskilled dichotomies, we argue skill itself has been used as a technology in the division of labor (Marx, 1990) to maintain patriarchal (Berg, 1994), and colonial hierarchies (Kumar, 2018). This genealogy helps situate how skill is conceptually operationalized alongside technology in contemporary politics. Through a systematic analysis of policy and public speech from four US presidents––from Clinton’s push to bridge the “digital divide” to Trump’s executive order to “combat the skills crisis”––we show how skills discourse is framed as a deficit issue in both democratic and republican administrations. By centering the conceptual roots of skill, this paper attempts to reclaim an understanding of skills as collective social knowledge that are essential to, and not separate from, technology (Veblen, 1914). Through this work, we hope to generate a broader discussion about the normative assumptions which tie the idea of skill to technological progress so we may re-imagine the kinds of collective social knowledge we need to produce a more just and equitable future.